Naskah-Naskah Fikih dan Praktek Keberislaman Masyarakat Adat di Lombok - Lalu Muhammad Ariadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Fikih manuscripts significantly influenced the Islamic societies typology are changing in Indonesia since the 17th century, i.e. Shirat al-Mustaqim and Tuhfah al-Mursalah. This study aims to analyze the influence of fikih manuscripts on indigenous people's religious patterns and also their religious practices in Lombok. By using the phenomenological approach to indigenous peoples in Central Lombok, this research found the text of fikih were brought to Lombok in the 17th century and the 18th century. This era built the practices of Islam by combining the tradition aspect and the Shafi'i's School paradigm. The manuscripts are using more Arabic-Malay (Jawi) script. They were spread out between Sasak people in Lombok between the 17th century and 18th century from the traders and Sasak people who travelled to several regions in Sulawesi and Sumatra. The manuscripts, such as Shirat al-Mustaqim and Tuhfah al-Mursalah give a strong character to the practices of fikih among indigenous peoples in Lombok. This can be seen on local implementation of wudu' and shalat. By the people in Lombok, this was known as Menjadi Sasak, Menjadi Islam.